Доля кінорежисера Гліба Затворницького - Безручко, О. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2008)
The article dedicated to dramatic fate of Hlib Zatvornytskyi, a film director of Kyiv film studio. The author analyzed his creative work as well as the cause of emigration in 1943 and the return home.